Landscape, Geopolitics, and National Identity in the Norwegian Thrillers Occupied and Nobel - Saunders Robert A. (Nordicom Review)
Focusing on the use of landscape in the Norwegian series Occupied (2015–2020) and Nobel (2016), this article examines the ways in which cityscapes and panoramas of the natural environment are employed as affective, as well as aesthetic tools for storytelling within a geopolitically inflected framework. Drawing on literature from popular geopolitics, geocriticism, and visual politics, my analysis interrogates the ways in which geopolitical codes and visions manifest via televisual fiction, reflecting a variety of insecurities associated with Norway's current position in world affairs, as well as contemporary challenges to Norwegian national identity. This article also discusses how these two series have adapted key geovisual elements of the what I deem the “near Nordic Noir” style to focus more explicitly on geopolitical questions, linking Occupied and Nobel to other geopolitically inflected series from Nordic Europe.